Evaluation of the Islamic Character Education Management System for Students at MTs Darul Ilmi Batang Kuis - Kalsum, Umi; Efendi Sipahutar, Romat (Pusdikra-Publishing.com, 2023)
This study evaluates the effectiveness of the Islamic character education management system at MTs Darul Ilmi Batang Kuis, focusing on its impact, challenges, and areas for improvement. The research employs a qualitative descriptive approach, involving semi-structured interviews, observations, and document analysis to gather insights from administrators, teachers, and students directly involved in the character education program. Findings indicate that the program has been effective in instilling core Islamic values such as honesty, respect, and responsibility, attributed to teacher role modeling, curriculum integration, and engaging activities. However, challenges such as limited resources, inconsistent teacher commitment, time constraints, and limited parental involvement affect the program’s consistency and depth. Key areas for improvement include enhanced teacher training, structured curriculum adjustments, increased parental engagement, and the development of a monitoring system to track students' progress in character development. The study concludes that while the program positively impacts student character, addressing these challenges can further enhance the effectiveness of Islamic character education at MTs Darul Ilmi Batang Kuis, contributing to the cultivation of morally grounded individuals aligned with Islamic principles.